2013
DOI: 10.3109/14767058.2013.791268
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury, risk factors and method of delivery – an 8-year analysis across two tertiary referral centers

Abstract: These results demonstrate that OASIS remains an important cause of maternal morbidity in contemporary obstetric practice. These results will likely be of value in risk management planning and patient debriefing in what is a highly litigious area of obstetrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
3
19
0
1
Order By: Relevance
“…Both forceps and vacuum delivery are known to be significant risk factors for OASI . In the present study, the OASI rate decreased significantly for both spontaneous deliveries and instrumental deliveries, which demonstrates that the STOMP principles applied at delivery can mitigate the risk of OASI even for deliveries that carry a higher overall risk.…”
Section: Discussionsupporting
confidence: 56%
“…Both forceps and vacuum delivery are known to be significant risk factors for OASI . In the present study, the OASI rate decreased significantly for both spontaneous deliveries and instrumental deliveries, which demonstrates that the STOMP principles applied at delivery can mitigate the risk of OASI even for deliveries that carry a higher overall risk.…”
Section: Discussionsupporting
confidence: 56%
“…The effect of vaginal delivery on anorectal function and defecation disorder is an important clinical issue . Our present findings in this regard in asymptomatic adults indicate that vaginal delivery is not independently associated with any anorectal HRM parameter.…”
Section: Discussionmentioning
confidence: 39%
“…Recently, a study has reported the association between BMI and anal pressures measured using conventional anorectal manometry . In addition, the vaginal‐delivery history is thought to affect anorectal parameters, as there have been a number of reports regarding defecation disorder and FI following delivery . However, detailed analyses of the influence of BMI and vaginal delivery on anorectal physiology are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant long term morbidity arises from third and fourth degree perineal tears, commonly called obstetric anal sphincter injuries (OASIS) . It has been demonstrated that the OASIS complicates 1.3% of natural vaginal deliveries, 3.7% of vacuum deliveries and 8.6% of forceps deliveries . Numerous studies have attempted to identify risk factors associated with OASIS following vaginal delivery of singletons .…”
Section: Introductionmentioning
confidence: 99%